Combining robotic exoskeleton and body weight unweighing technology to promote walking activity in tetraplegia following SCI: A case study. (2nd January 2020) - Chang, Shuo-Hsiu; Zhu, Fangshi; Patel, Neel; Afzal, Taimoor; Kern, Marcie; Francisco, Gerard E.
Abstract : Context: To investigate the feasibility of combining the lower-limb exoskeleton and body weight unweighing technology for assisted walking in tetraplegia following spinal cord injury (SCI). Findings: A 66-year-old participant with a complete SCI at the C7 level, graded on the American Spinal Injury Association Impairment Scale (AIS) as AIS A, participated in nine sessions of overground walking with the assistance from exoskeleton and body weight unweighing system. The participant could tolerate the intensity and ambulate with exoskeleton assistance for a short distance with acceptable and appropriate gait kinematics after training. Conclusion: This report showed that using technology can assist non-ambulatory individuals following SCI to stand and ambulate with assistance which may promote general physical and psychological health if used in the long term.